History of the Jewish National Military Unit Project as part of the Red Army in 1942-1943 - Bezugolny, Alexey Yu (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
During the Great Patriotic War, over fifty national military units were formed as part of the Red Army. In addition, military units were composed of foreign citizens. Based on documentary sources, the article examines the history of the unrealized project of forming a Jewish Army in early 1943. The analysis is based on the set of documents revealed by the author in the fund of the Chief Directorate for the Formation and Staffing of Troops (Glavupraform) of the Red Army in the Central Archive of the Ministry of Defense of the Russian Federation. The article examines the peculiarities of Soviet Jews’ position in the Red Army, associated with their high representation among the commanding staff. From the beginning of the war, the Jewish public debated the formation of a Jewish military unit as part of the Red Army. This issue was close to realization only once. The appeal of a serviceman, G.L. Zilberman, was received by E.A. Shchadenko, the Deputy People's Commissar of Defense, who on January 15, 1943, prepared a draft resolution of the State Defense Committee for the formation of a force. The article examines the circumstances of the preparation of this document and analyzes the reasons why it was not implemented.